Turning Back the Direction of Canadian Foreign Aid - Muzamhindo, Masimba (Université Saint-Paul / Saint Paul University, 2019)
Canad foreign aid has been a fixture in Canadian foreign policy for close to 70 years. The end of the autonomous Canadian Internationa Development Agency (CIDA) and the creation of Global Affairs Canada (GAC) has brought about the belief that Canadian foreign aid has now achieved policy coherence. This belief is found through the Feminist International Assistance Policy (FIAP) where aid will address gender inequality in all its functions. This thesis looks at the reasons for why policy incoherence has existed in Canadain aid and blames it on three approaches that have confused foreign aid objectives. It proposes the need to focus on Private Sector Development as a remedy for policy coherence and as a remedy for an aid system that is under the influence of the whole of Canadian Foreign Policy. The plan for Private Sector Development is guided by Development Ethicist Amartya Sen's Capability Approach. The thesis shows how this looks practically in one of the top 20 countries that receive Canadian aid, Mozambique.
Keywords: Capability Approach; Foreign Aid; Canadian International Development Agency; Global Affairs Canada; Foriegn Policy; Feminist International Assistance Program; Private Sector Development; Mozambique; International Development